Ecological insight of seasonal plankton succession to monitor shellfish aquaculture ecosystem interactions - Sharpe, Hannah; Gallardi, Daria; Gurney-Smith, Helen; Guyondet, Thomas; McKindsey, Christopher W.; Lacoursière-Roussel, Anaïs (Frontiers in Marine Science, 2024)
Introduction Bivalve aquaculture has direct and indirect effects on plankton communities, which are highly sensitive to short-term (seasonal, interannual) and long-term climate changes, although how these dynamics alter aquaculture ecosystem interactions is poorly understood. Methods We investigate seasonal patterns in plankton abundance and community structure spanning several size fractions from 0.2 µm up to 5 mm, in a deep aquaculture embayment in northeast Newfoundland, Canada. Results Using flow cytometry and FlowCam imaging, we observed a clear seasonal relationship between fraction sizes driven by water column stratification (freshwater input, nutrient availability, light availability, water temperature). Plankton abundance decreased proportionally with increasing size fraction, aligning with size spectra theory. Within the bay, greater mesozooplankton abundance, and a greater relative abundance of copepods, was observed closest to the aquaculture lease. No significant spatial effect was observed for phytoplankton composition. Discussion While the months of August to October showed statistically similar plankton composition and size distribution slopes (i.e., food chain efficiency) and could be used for interannual variability comparisons of plankton composition, sampling for longer periods could capture long-term phenological shifts in plankton abundance and composition. Conclusions provide guidance on optimal sampling to monitor and assess aquaculture pathways of effects.